Growth and some period yield characteristics of denizli x leghorn crosses (f2) - Mustafa Garip; Mehmet Nizamlioglu; Ercan Kurar; AlperYilmaz; Tamer Çağlayan; Süleyman Dere; Zafer Bulut; Yusuf Ozsensoy; Varol Kurtoglu (Eurasian Journal of Veterinary Sciences)
Aim: This study was carried out to determine some production characteristics of F1 and F2 Denizli x Leghorn populations including hatching weight, growth performance, live weights of the growing period, egg gravity and egg weight. Material and Methods: Ten Denizli roosters and 30 Leghorn hens were used for generation of the base population. In the first generation (F1, 15 males and 68 females were produced. A total of 475 males and 451 females were produced in the second generation (F2), and whose production data were evaluated based on the 32 weeks of periods. Results: In F2 population, numbers and percentages of egg yield were found to be 99.61 and 56.21% in the first 180-day period. Hatching weights were determined as 40.94 and 30.80 g in F1 and F2 generations, respectively. Significant differences were observed in weights of F1 and F2 animals at the growing period (p<0.001). In addition, the second generation live weights were measured as 1814.60 g in females and in 1900.00 g in males at the end of 32nd week (p<0.001). Egg weight and specific gravity values were calculated as 47.81 g and 1.08 respectively in the F2 population. Conclusion: It was concluded that Denizli breed, a native genetic resource, seems to be suitable and candidate chicken breed for future hybridization studies. Furthermore, there is need for further detailed studies to evaluate Denizli crosses with layer or broiler breeds for this production characteristic.